Tomato response to potassium fertirrigation and black polyethylene cover - Sampaio, Regynaldo Arruda; Fontes, Paulo Cezar Rezende; Sediyama, Carlos Sigueyuki (Pesquisa Agropecuaria Brasileira, 1999)
The aim of this work was to determine the effects of fertirrigation with potassium and black polyethylene cover on tomato. A field experiment was carried out on a cambic yellowish podzolic at the Universidade Federal de Viçosa, in Viçosa, MG, Brazil. The treatments, with five replicates, following a randomized block design, were: (A) manual application of 40% of recommended K rate at the seedling transplantation row and manual sidedress application of 60%; (B) manual application of 40% of recommended K rate at the seedling transplantation row and 60% by fertirrigation; (C) similar procedure to B but with black polyethylene cover; (D) application of 100% of K rate by fertirrigation and (E) similar procedure to D but with black polyethylene cover. Treatments B, C, D and E were drip irrigated. Tomato yields were higher with K application by fertirrigation than using the manual fertilization method, but the tomato yields were not influenced by K partial or total fertirrigation neither by black polyethylene cover. The NO3–N, organic-N, K, Ca and Mg concentrations on leave petioles were not influenced by treatments.